TREND CYCLE ANALYSIS ON FAST FASHION PRODUCTS - Ni Kadek Yuni Diantari (Yayasan Sinergi Widya Nusantara, 2021)
Purpose: trend cycles need to be understood to know the developments and changes in trends infast fashion as well as consumer considerations in consuming fast fashion products.Research methods: Trend changes in such a short time need to be analyzed further through trendstages, trend cycles, and trend differentiation that occurs in fast fashion. To analyze the trend in fastfashion products, a qualitative descriptive method was conducted in which the research processconsisted of collecting and compiling data, analyzing and interpreting phenomena.Findings: Trends provide trends in fast fashion products such as colors, styles, themes, motifs,and cuts/silhouettes. In general, fashion trends generally only recognize two seasons, includingspring/summer (spring/summer) and autumn/cold (fall and winter). Fast fashion has 52 trends in ayear or about once a week. In fast fashion, trend changes are influenced by the stages of the fashioncycle, fashion flows, trend differentiation, and trend adopters.Implications: Fast fashion is a design, manufacturing and marketing method that focuses onproducing large quantities of clothing quickly and at affordable prices. Fast fashion products arealways influenced by trends.